Perintal survival of infants weighing more thatn 500g whose mothers died in the puerperium before being discharged: a retrospective descriptive study at Charlotte Maxeke Johannesburg academic hospital from 2003 to 2012 - Blaise, Bucyibaruta Joy (My University, 2015)
A growing body of evidence confirms a slow reduction in neonatal deaths, of which the majority occur in the early neonatal period. The burden of perinatal deaths is heavy in developing countries where the perinatal death rate is about five times higher than its rate in developed countries. Similarly, about 99% of maternal deaths occur in developing countries. However, to the best of our knowledge, little is known about perinatal outcomes of infants born to mothers who die from complications of childbirth. This gap in the existing literature motivated us to undertake the study, which aimed to investigate the perinatal outcomes of infants born to mothers who died from complications of childbirth at Charlotte Maxeke Johannesburg Academic Hospital. It consisted of a retrospective study, over a 10 year period, on infants weighing 500 g and more or with gestational age of 22 weeks and above born to mothers who died from complications of childbirth. A sample size of 122 mothers and 128 infants eligible were analysed through quantitative methods. Among these infants, 85 (66.4%) were born alive. The identified top four obstetrical causes of maternal deaths were: non-pregnancy related infections including HIV/AIDS, Hypertensive disorders of pregnancy, pre-existing maternal diseases and postpartum haemorrhage. HIV and hypertension accounted for more than 50% of maternal deaths. The findings revealed that emergency caesarean section was high (70%) and the perinatal survival rate was 55%. Maternal parity, Apgar scores at one minute and mode of delivery were identified as the main predictors which were statistically associated with perinatal survival, with correlation coefficient of + 0.7 (P=0.030), + 0.4 (P=0.000) and + 0.1 (P=0.002) respectively. Concerning infants born alive, early neonatal survival rate was 84%. Apgar score at five minutes and maternal parity were the sole predictors that were statistically associated with neonatal outcomes, with correlation coefficient of +0.3 (P=0.000) and + 0.1 (P=0.019). These findings demonstrated that with appropriate labour monitoring, adequate neonatal resuscitation and good perinatal care, the majority of those infants would be born alive with four out of five surviving to hospital discharge.
Dissertation submitted in partial fulfilment of requirements for a Master of Medicine Degree in Paediatrics and Child Health (MMED PAED)
Keywords: Perinatal Death; Postpartum Period; Maternal Death